Wychowawczy, edukacyjny i społeczny wymiar wileńskich cechów doby wczesnonowożytnej. Towarzysz w służbie mistrza i cechu - Manyś, Bernadetta (Biuletyn Historii Wychowania, 2024)
In the following paper I would like to analyze educational, social and upbringing related dimensions of Vilnius guilds, employing apprentices. They not only worked but, participating in manufacturing of goods, they also prepared themselves for the profession. In this article, I take a look at the functioning of this group in the structures of guilds and workshops run by Vilnius craftsmen. The question arises what was expected of them as members of craft workshops and guilds. How the companions’ dependence on the master, for whom they worked, changed. In addition, there is an issue of the role of practice – the journey that had to be made in the case of some professions and the skills acquired in the process. The following research does not have an ambition of being a holistic study of the issue; it is a revision and a supplement to Józef Morzy’s research where he partly analyzed craft guilds in Vilnius, in terms of essential work skills. In order to explain these issues, the statutes of the craft guilds were analyzed in Vilnius, one of the biggest cities of the Polish–Lithuanian Commonwealth, in the early modern period.